Awareness of user mobility in Named Data Networking for IoT traffic under the push communication mode. (April 2023) - Alkwai, Lamia; Belghith, Abdelfettah; Gazdar, Achraf; AlAhmadi, Saad
Abstract: The current proliferation of Internet of Things (IoT) mobile devices has helped to show the limitations of the IP model to support content-based applications and networking. Named Data Networking (NDN) appears to be more in line with the IoT framework and vision. However, NDN still lacks native integration of effective user mobility management to meet the requirements of various latency-sensitive applications such as real-time streaming and embraces the continued proliferation of smart phones and mobile devices. In this paper, we first propose to integrate a push communication model into NDN to better suit real time streaming applications. We propose the use of persistent interests (PI) to create a streaming like capability in NDN and significantly reduce the interests traffic within the network. Producer and consumer mobility handling for seamless and continuous data flows becomes a real challenging issue under the PI framework. We propose PIMM a radically new anchorless mobility management approach for NDN. PIMM integrates efficient mechanisms for the mobility of both producer and consumer, and sustains high mobility environments as well as requirements of latency sensitive applications. PIMM is implemented in the de facto NDN simulator (ndnSIM2.1), evaluated and benchmarked with existing NDN producer mobility management solutions. Simulations results clearly show the efficiency of PIMM and highlight its superiority in terms of handoff latency, data loss, and data delay jitter.